1972
DOI: 10.1172/jci106876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dibutyryl Cyclic Adenosine 3′,5′-Monophosphate and Parathyroid Extract on Calcium and Phosphorus Metabolism in Hypoparathyroidism and Pseudohypoparathyroidism

Abstract: A B S T R A C T It has been proposed previously that the metabolic defect in pseudohypoparathyroidism which accounts for parathyroid hormone unresponsiveness is an absence or abnormal form of the adenyl cyclase system in kidney and presumably in bone. To determine whether there is an associated defect in the response mechanism to cyclic adenosine 3',5'-monophosphate (cyclic AMP), the effects of parathyroid extract (PTE), and dibutyryl cyclic AMP were compared in patients with either surgical hypoparathyroidism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1973
1973
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…Our experiments are at variance with those of Nagata and Rasmussen (9), who found that Fig. 4 Previous studies have shown that the phosphaturic action of PTH in TPTX rats can be produced through infusion of either dibutyryl cyclic AMP (2,(28)(29)(30) or theophylline (28). In addition, it has been reported that the phosphaturic response to both PTH and dibutyryl cyclic AMP is blunted in the D-deficient rat (2).…”
Section: Methodssupporting
confidence: 47%
“…Our experiments are at variance with those of Nagata and Rasmussen (9), who found that Fig. 4 Previous studies have shown that the phosphaturic action of PTH in TPTX rats can be produced through infusion of either dibutyryl cyclic AMP (2,(28)(29)(30) or theophylline (28). In addition, it has been reported that the phosphaturic response to both PTH and dibutyryl cyclic AMP is blunted in the D-deficient rat (2).…”
Section: Methodssupporting
confidence: 47%
“…The impairment of the adenylate cyclase system in PHP is well known (Chase et al 1969;Bell et al 1972). Drezner et al (1973) classified PHP into 2 types; impairment of an increase in intracellular cAMP (Type I), an inability of intracellular CAMP to initiate the chain of metabolic events (Type II).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the role of cAMP in mediating the phosphaturic response of PTH at the kidney level in man and experimental animals (1 1, 12, 16,25,30). Administration of cAMP has been shown to mimic the phosphaturic effect of PTH in vivo (4,30), and in vitro (3,15). An increase in adenylate cyclase activity and accumulation of intracellular cAMP after PTH administration have been demonstrated (16,26).…”
Section: Resultsmentioning
confidence: 99%